2017
DOI: 10.22146/ijc.22273
|View full text |Cite
|
Sign up to set email alerts
|

A New Polyketide from the Endophytic Fungus <i>Penicillium chermesinum</i>

Abstract: A new polyketide derivative, 2-chloro-3,4,7-trihydroxy-9-methoxy-1-methyl-6H-benzo[c]chromen-6-one (1) 2-chloro-3,4,7-trihydroxy-9-methoxy-1-methyl-6H-benzo[c]chromen-6-one. Senyawa 1 menunjukkan aktivitas sitotoksisitas lemah terhadap sel kanker HepG2,71 µM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…Previous reports, showed that Penicillium genus has many important biological activities (Hyde and Soytong 2008 ). Moreover, Kittakoop’s group discovered a new polyketide (2-chloro-3,4,7-trihydroxy-9-methoxy-1-methyl-6 H -benzo[c]chromen-6-one) from the Penicillium chermesinum which has shown to be cytotoxic against four cancer cell lines, which are HuCCA-1, HepG2, A549 and Moult-3 cell lines (Darsih et al 2017 ). This data supports that the Penicillium sp.…”
Section: Resultsmentioning
confidence: 99%
“…Previous reports, showed that Penicillium genus has many important biological activities (Hyde and Soytong 2008 ). Moreover, Kittakoop’s group discovered a new polyketide (2-chloro-3,4,7-trihydroxy-9-methoxy-1-methyl-6 H -benzo[c]chromen-6-one) from the Penicillium chermesinum which has shown to be cytotoxic against four cancer cell lines, which are HuCCA-1, HepG2, A549 and Moult-3 cell lines (Darsih et al 2017 ). This data supports that the Penicillium sp.…”
Section: Resultsmentioning
confidence: 99%
“…Endophytic fungi are microorganisms that live below the epidermal cell layer in plant tissues without causing any symptoms of disease. They form symbiotic relationships with their host plants, producing secondary metabolites that protect against pathogen attacks [ 6 , 7 ]. Substances produced by endophytic fungi have a variety of effects on plants, including growth promotion, increased resistance to disease, and an enhanced ability to withstand environmental stress [ 8 ].…”
Section: Introductionmentioning
confidence: 99%